Economic evaluation and comparison of migration paths for the smart grid using two case studies. Issue 11 (November 2020) - Flore, Agnetha; Marx Gómez, Jorge; Uslar, Mathias
Abstract: Today, European utility companies are facing the conversion of their power grids from a previously centrally controlled supply to a then decentralized supply. These changes are necessary to achieve the climate targets. In order to create a decentralized power grid, the integration of modern information and communication technologies (ICT) and other hardware is necessary. On the one hand, the utilities must know which paths they can take to make their power grid intelligent, but on the other hand it is also crucial to know the costs involved. In this contribution we outline a possible model for technological migration paths with a corresponding economic analysis based on German and European case studies. Abstract : Economics; Electrical engineering; Energy; Systems engineering; Environmental economics; Environmental engineering; Migration paths; Smart grids; Cost benefit analysis; Extrapolation; Case study.